Impact of Overnight Wear of Orthokeratology Lens on Thickness of Tear Film Lipid Layer in Children with Myopia - Chen, Yuanyuan; Liu, Ming; Lu, Huayi; Zhang, Yong; Luo, Dan; Pan, Hongbiao; Wan, Chuan; Szentmáry, Nóra; Shi, Lei (Klinische Monatsblätter für Augenheilkunde, 2022)
Background To elucidate the influence of overnight wear of orthokeratology (OOK) lenses on the thickness of the tear lipid layer (LLT).Methods We conducted a retrospective cross-sectional study of children who visited The First Affiliated Hospital of USTC between July and September 2021. LLT and blinking dynamics were assessed. Diopters and corneal topography were also recorded.Results The number of children enrolled in this program was 402 (804 eyes). One hundred and seventy-one children (342 eyes, 79 males and 92 females) aged 4 – 17 years (10.59 ± 2.54 years) who never wore OOK were included in the control group, while 231 children (462 eyes, 121 males and 110 females) aged 7 – 18 years (11.09 ± 2.24 years) who wore OOK for more than 1 week were included in the observation group. Compared to the control group with an LLT of 58.5 ± 18.19 nm, the OOK group exhibited a significant decrease in the LLT value to 54.42 ± 17.60 nm. In addition, the LLT in females was significantly thicker than that in males in both the control (male 54.78 ± 16.56 nm, female 61.70 ± 18.95 nm) and observation groups (male 51.88 ± 16.68 nm, female 57.21 ± 18.18 nm). It is worth noting that the influence of wearing OOK on the LLT value was only detected up to 18 months. Eighteen months later, there was almost no difference in LLT between the control and observation groups. We also noted that there was no change in LLT correlated to the surface regularity index/surface asymmetry index.Conclusion Wearing OOK can affect tear film LLT within the first 18 months after wear. More attention should be given to children wearing OOK for less than 18 months, especially males.
Keywords: tear film; lipid layer thickness; overnight orthokeratology; myopia